An analysis of the smallholder farmers' cassava (Manihot esculenta Crantz) value chain through a gender perspective: the case of Dak Lak province, Vietnam - Xuan Hoa Ao; Trinh Vuong Vu; Khac Dong Le; Sopin Jirakiattikul; Kuaanan Techato (Cogent Economics & Finance, 2019)
Many rural women, who are faced with the challenges of low rural incomes and gender inequality, improve their role in the farming system based on participation in the agricultural value chain thus enhancing agricultural productivity, household income and sustainable development. This study investigates the factors which affect participation in the production of cassava in Dak Lak Province and decisions in relation to the cassava value chain from a gender perspective. Data were obtained through a questionnaire-based survey of 300 household farmers, in-depth interviews with key informants, and focus group discussions. Probit and ordinary least squares regression models in a two-stage Heckman model were adopted to determine the factors affecting females' decisions to participate in cassava cultivation, their level of participation and their participation in other stages of the cassava value chain. The survey results show that men are prominent in all stages of cassava production but there is a more equal gender dynamic in both cassava production participation decisions and decisions relating to the quantity of cassava to be supplied for commercial purposes. This article draws attention to the continuing role challenges of female smallholder farmers, but also shows how women's empowerment is contingent on equity dynamics in the household as well as social norms in the community and wider society.
Keywords: 330; cassava value chain; female; gender equality; male; smallholder farmer